2011
DOI: 10.1002/qj.894
|View full text |Cite
|
Sign up to set email alerts
|

Multidecadal and interannual changes of stationary Rossby waves

Abstract: Changes in stationary Rossby waves (SRW) are connected to regional climate change and the propagation of these waves has a large influence on the evolution and development of the general circulation. Since the late 1970s and early 1980s many studies have noted a major shift in the structure of large-scale circulation occurring in both hemispheres. This paper explores the changes in the SRW pattern and their propagation associated with these climate shifts. First, multidecadal changes in SRW activity are examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…This is consistent with studies showing a weakening in the meridional circulation, and consequent large-scale observed changes in the wintertime subtropical jet (e.g. Frederiksen and Frederiksen 2007;Freitas and Rao 2011). This is a seemingly stronger signal than for the vertically integrated mass streamfunction "Intensity" defined by Nguyen et al (2013).…”
Section: Slow-external Modessupporting
confidence: 86%
“…This is consistent with studies showing a weakening in the meridional circulation, and consequent large-scale observed changes in the wintertime subtropical jet (e.g. Frederiksen and Frederiksen 2007;Freitas and Rao 2011). This is a seemingly stronger signal than for the vertically integrated mass streamfunction "Intensity" defined by Nguyen et al (2013).…”
Section: Slow-external Modessupporting
confidence: 86%
“…The differences in each one of the cases can be more clearly seen and properly analyzed in a superimposed map [35]. Thus, the contours in red are for weak HC cases, superimposed on the contours in blue for strong HC cases.…”
Section: Latitudementioning
confidence: 94%
“…Several studies have shown that, in the late 1970s and early 1980s, a major shift occurred in the structure of large-scale circulation in both hemispheres (e.g., Freitas and Rao, 2011;Frederiksen and Frederiksen, 2005;2007 -hereafter FF05, FF07, respectively). In the Southern Hemisphere (SH), FF05 and FF07 found that there were quite large changes in thermal structure and atmospheric circulation, between the periods of 1949-1968 and 1975-1994.…”
Section: Introductionmentioning
confidence: 99%